Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity

Oxidative coupling of methane over La-promoted CaO catalysts: influence of precursors and catalyst preparation method - Rane, Vilas H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2010)
The oxidative coupling of methane to C(2) hydrocarbons has been studied over a series of La-promoted CaO (La/Ca = 0.05) catalysts, prepared using different precursor salts for CaO and La(2)O(3) (viz. acetates, carbonates, nitrates and hydroxides) and catalyst preparation methods (viz. physical mixing of precursors, co-precipitation using ammonium carbonate/sodium carbonate as a precipitating agent), under different reaction conditions (temperature: 700-850 degrees C, CH(4)/O(2) ratio: 4.0 and 8.0, and GHSV: 51360 cm(3).g(-1).h(-1)). The surface area and surface basicity/base strength distribution of the catalysts have also been investigated. The surface properties and catalytic activity/selectivity of the La-promoted CaO catalysts vary from catalyst to catalyst depending on the catalyst precursors used and catalyst preparation method. The basicity/base strength distribution is strongly influenced by the precursors (for CaO and La(2)O(3)) and catalyst preparation method. Basicity (total and strong basic sites measured in terms of CO(2) chemisorbed at 50 degrees C and 500 degrees C, respectively) observed for the catalyst prepared by co-precipitation method is higher than that of the catalysts prepared by physical mixing method. The catalysts prepared by the nitrates of La- and Ca- and co-precipitated by the solution of sodium carbonate and ammonium carbonate exhibit different catalytic performance in OCM. The finding that no direct relationship between the surface basicity and catalytic activity/selectivity in OCM exists indicates that basicity is not solely responsible for obtaining high selectivity to C(2) hydrocarbons.
Keywords: basicity distribution; La-promoted CaO catalysts; oxidative coupling of methane